Participation rates for organized colorectal cancer screening programmes: an international comparison. (September 2015) - Klabunde, Carrie; Blom, Johannes; Bulliard, Jean-Luc; Garcia, Montse; Hagoel, Lea; Mai, Verna; Patnick, Julietta; Rozjabek, Heather; Senore, Carlo; Törnberg, Sven
Objective: Participation, an indicator of screening programme acceptance and effectiveness, varies widely in clinical trials and population-based colorectal cancer (CRC) screening programmes. We aimed to assess whether CRC screening participation rates can be compared across organized guaiac fecal occult blood test (G-FOBT)/fecal immunochemical test (FIT)-based programmes, and what factors influence these rates. Methods: Programme representatives from countries participating in the International Cancer Screening Network were surveyed to describe their G-FOBT/FIT-based CRC screening programmes, how screening participation is defined and measured, and to provide participation data for their most recent completed screening round. Results: Information was obtained from 15 programmes in 12 countries. Programmes varied in size, reach, maturity, target age groups, exclusions, type of test kit, method of providing test kits and use, and frequency of reminders. Coverage by invitation ranged from 30–100%, coverage by the screening programme from 7–67.7%, overall uptake/participation rate from 7–67.7%, and first invitation participation from 7–64.3%. Participation rates generally increased with age and were higher among women than men and for subsequent compared with first invitation participation. Conclusion: Comparisons among CRC screening programmes should be made cautiously, given differences in organization, target populations, and interpretation of indicators. More meaningful comparisons are possible if rates are calculated across a uniform age range, by gender, and separately for people invited for the first time vs. previously.